2014
DOI: 10.1186/1471-227x-14-17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motorcycle helmet type, components and fixation status on facial injury in Klang Valley, Malaysia: a case control study

Abstract: BackgroundThe effectiveness of helmets in reducing the risk of severe head injury in motorcyclists who were involved in a crash is well established. There is limited evidence however, regarding the extent to which helmets protect riders from facial injuries. The objective of this study was to determine the effect of helmet type, components and fixation status on the risk of facial injuries among Malaysian motorcyclists.Method755 injured motorcyclists were recruited over a 12-month period in 2010–2011 in southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 23 publications
0
24
0
6
Order By: Relevance
“…Studies conducted in Western countries and Taiwan [17,[20][21][22][23][24][25] have reported that full-coverage helmets protect from head injuries. In line with previous results, our results indicated that standard helmets have a highly protective role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in Western countries and Taiwan [17,[20][21][22][23][24][25] have reported that full-coverage helmets protect from head injuries. In line with previous results, our results indicated that standard helmets have a highly protective role.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have attempted to examine the effects of different helmet types on head and neck injuries. For example, studies [17][18][19][20][21][22] have reported that riders wearing open-face or half helmets had an increased risk of sustaining facial and neck injuries compared with riders wearing full-face helmets. Rice et al [23] concluded that novelty helmet or nonstandard helmet use was associated with an increased risk of fatal injuries compared with full-face helmet use after adjustment for speed and other risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Only secured helmets which remain attached to the cranium during a collision will provide some protection to the maxillofacial area. 9 Thus, to decrease the incidence of midface trauma, we believe more attention should be given by enforcement agencies on, existing regulations regarding the type of helmet and helmet safety protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha demostrado que un motociclista con casco reduce un 25% la probabilidad de resultar lesionado y un 30% si utiliza otro equipo protector (como ropa de cuero), por lo que en conjunto con todo el equipo los riesgos se reducen cerca del 50% 9 . La prevalencia del uso del casco varía alrededor del mundo; por ejemplo, la literatura muestra valores en países emergentes del 16.2% en Laos 20 , el 40% en Argentina 21 , el 48% en Camboya 22 y el 88.7% en Malasia 23 . Las variaciones se deben a factores culturales, socioeconómicos, ambientales, temporales y normativos propios de cada región [24][25][26][27] .…”
Section: Discussionunclassified
“…Esto apoya la creencia de que las mujeres tienen tasas más bajas de participación en los accidentes, en particular entre los conductores jóve-nes. Tales diferencias de sexo se han encontrado en los análisis de colisiones de numerosas investigaciones sobre motociclistas 23,32 . Sin embargo, la prevalencia de consumo de alcohol, del 13.73%, es mucho menor que las encontradas en otros estudios 33 que indican que entre el 41 y el 80% de los conductores de motocicleta lesionados dieron positivo al consumo de alcohol.…”
Section: Discussionunclassified